Age-Related Macular Degeneration Cases in Prof. RD Kandou General Hospital, Manado - Inga Santoso; Vera Sumual (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To report the data of patients with age-related macular degeneration (AMD) at Vitreo-Retina Division of Ophthalmology Department of Prof. RD Kandou General Hospital, Manado.Methods: This study was descriptive retrospective using medical records at the OphthalmologyDepartment of Prof. RD Kandou General Hospital, Manado period of January 2014 until June 2016.The subjects of research were the medical records of patients diagnosed with age-related maculardegeneration.Results: Of 27 patients, 14 (51.9%) were male and 13 (48.1%) were female with age ranging from 41to 81 years old. By type of AMD, the distribution was 85.2% dry and 14.8% wet AMD. Among therisk factors of AMD were hypertension in 12 patients (44.4%), diabetes mellitus in 2 patients (7.4%),and both hypertension and diabetes mellitus in 3 patients (11.1%).Conclusion: The number of patients diagnosed with AMD was 27 patients, with insignificant genderdifference. Most of the patients fell on the 61 to 71 years old group (48.2%), with majority type weredry AMD. Hypertension was the most influential risk factor.